The Effect of Compensation Policy and Work Discipline on Nurse Productivity at dr. H. Marzoeki Mahdi Mental Hospital Bogor in 2023 - Febrianti, Icha Tiara Devi; Andriani, Helen (UI Scholars Hub, 2024)
Health worker productivity problems due to suboptimal institutional management still often occur, including at the dr. H. Marzoeki Mahdi Mental Hospital (RSJMM). Nurses are the most significant number of health workers in hospitals with a high level of patient intervention; inappropriate treatment risks decreasing work productivity. This research aims to analyze the effect of financial compensation, non-financial compensation, and work discipline on nurse productivity at RSJMM. The research study used a quantitative approach by distributing questionnaires to 205 nurses. The results showed partially (1) financial compensation has no significant effect on nurse productivity (Sig. value 0.953 > 0.05, β=0.002); (2) Non-financial compensation has a positive and significant effect on nurse productivity (Sig. value 0.016 < 0.05, β=0.073); (3) Work discipline has a positive and significant effect on nurse productivity (Sig. value 0.000 < 0.05, β=0.293). The work discipline variable (0.293) most dominantly affects nurse productivity. Simultaneously, the three variables have a moderate effect on nurse productivity of 0.576 or 57.6%, while other variables influenced other variables influenced the remaining 42.4%. These results have limitations that are based on respondent's perceptions. It is suggested that hospitals need to optimize nurse productivity by improving hospital facilities, training, educational opportunities, transparency and fairness of compensation systems, recognition and feedback for employee performance, and compliance with work discipline.